Neuroanesthesia Management in Pediatric with Traumatic Brain Injury Due to Gunshot Wound - Nugroho A; Bisri DY; Rachman IA; Halimi RA (Open Access Emergency Medicine, 2025)
Andy Nugroho, Dewi Yulianti Bisri, Iwan Abdul Rachman, Radian Ahmad Halimi Department of Anesthesiology and Intensive Therapy, Universitas Padjadjaran, Bandung, IndonesiaCorrespondence: Andy Nugroho, Email andy23002@mail.unpad.ac.idAbstract: Traumatic brain injury (TBI) in the pediatric population is a major cause of morbidity and mortality. Between various etiologies of TBI, gunshot wounds occupy a unique characteristic and apprehensive place. We report a clinical case of a TBI due to a gunshot wound in Indonesia. A 4-year-old girl complained of a painful head and vomiting after sustaining a gunshot wound to the head. The patient was presented with a pediatric Glasgow Coma Scale (pGCS) score of E3V4M5 and was hemodynamically stable Multislice computerized tomography (MSCT) revealed a bullet lodged in the left temporal lobe, a subdural hematoma in the left frontoparietal-temporooccipital, an intracranial hemorrhage in the left temporoparietal region, and a midline shift to the right by 0.7 cm. The patient underwent craniotomy for subdural hematoma evacuation and bullet evacuation. Stable hemodynamics and brain relaxation conditions were achieved during surgery. Postoperative recovery in the pediatric intensive care unit (PICU) was uneventful, and the patient was discharged with improved neurological status (pGCS E4V5M6) without complications. The case highlights the successful management of a pediatric patient with traumatic brain injury due to a gunshot wound through a multidisciplinary and tailored approach focusing on hemodynamic stability, intracranial pressure management, early posttraumatic seizure, and infection prophylaxis to ensure a positive outcome. Given the scarcity of reported cases in low- and middle-income settings, this report provides valuable insights into the optimal management of pediatric gunshot-related TBIs.Keywords: gunshot wound, neuroanesthesia, pediatric, traumatic brain injury